One-Pot Synthesis of Pd Nanoparticles Supported on Carbide-Derived Carbon for Oxygen Reduction Reaction - Madis Lüsi; Heiki Erikson; Maike Käärik; Helle-Mai Piirsoo; Jaan Aruväli; Arvo Kikas; Vambola Kisand; Jaan Leis; Kaupo Kukli; Kaido Tammeveski (Nanomaterials, 2024)
We explored two methods for synthesizing Pd nanoparticles using three different carbide-derived carbon (CDC) support materials, one of which was nitrogen-doped. These materials were studied for oxygen reduction reaction (ORR) in 0.1 M KOH solution, and the resulting CDC/Pd catalysts were characterized using TEM, XRD, and XPS. The citrate method and the polyol method using polyvinylpyrrolidone (PVP) as a capping agent were employed to elucidate the impact of the support material on the final catalyst. The N-doping of the CDC material resulted in smaller Pd nanoparticles, but only in the case of the citrate method. This suggests that the influence of support is weaker when using the polyol method. The citrate method with CDC1, which is predominantly microporous, led to a higher degree of agglomeration and formation of larger particles in comparison to supports, which possessed a higher degree of mesoporosity. We achieved smaller Pd particle sizes using citrate and NaBH4 compared to the ethylene glycol PVP method. Pd deposited on CDC2 and CDC3 supports showed similar specific activity (SA), suggesting that the N-doping did not significantly influence the ORR process. The highest SA value was observed for CDC1/Pd_Cit, which could be attributed to the formation of larger Pd particles and agglomerates.